THE IMPLEMENTATION OF THE POSYANDU (ELDERLY) PROGRAM AT TOARI COMMUNITY HEALTH CENTER: A REVIEW FROM DUNCAN'S PROGRAM EFFECTIVENESS PERSPECTIVE - Amalia, Dea Rizky; Hidayat, Rahmat; Yunita, Andi; Fuzail, Muhammad (Jurnal Administrasi Negara, 2025)
This study aims to evaluate the implementation of the Elderly Posyandu Program at Toari Health Center through the lens of Duncan’s program effectiveness framework, which comprises three key indicators: goal achievement, integration, and adaptation. The evaluation is particularly relevant in light of the growing elderly population in rural areas and the limited access to inclusive and sustainable healthcare services. A qualitative descriptive method was employed to comprehensively describe the program's implementation based on empirical data obtained through in-depth interviews, participant observation, and document analysis. The findings indicate that the program demonstrates partial effectiveness. In terms of goal achievement, activities often experience delays, elderly participation remains low, and home visits are not conducted regularly. Regarding integration, stakeholder collaboration is suboptimal, and socialization efforts are still incidental. In the adaptation dimension, infrastructure and support facilities are inadequate and do not yet meet elderly-friendly service standards. This study’s contribution is twofold: it not only provides a contextual overview of elderly health program implementation in rural areas, but also enriches the program evaluation literature within the field of public administration by operationalizing Duncan’s effectiveness model. The implications of these findings highlight the importance of improving service management, strengthening collaborative governance, and advancing evidence-based policy reforms to enhance the quality of public services, particularly within the community-based public health sector.